IDENTIFICAÇÃO DE CARACTERÍSTICAS DE PERSONALIDADE EM GRUPOS CLÍNICOS POR MEIO DA ANÁLISE QUANTITAVIA E QUALITATIVA DO PSICODIAGNÓSTICO MIOCINÉTICO – PMK - ARSUFFI, EMANUELLE DOS SANTOS (2019)
Psychological evaluation is a practice that can be used in the different psychologist's areas of activity, such as: school, health institutions, social, clinical, sports, among others. The professional should make use of different techniques and instruments, being the most used, interviews and psychological tests. Through the tests it is possible to evaluate different psychological characteristics, such as attention, memory, intelligence, personality, among others. Personality is one of the most valued features that has been extensively studied. One of the ways to evaluate personality is s Myokinetic Psychodiagnosis – MKP. This research aims to raise personality characteristics in different clinical groups through MKP. A total of 122 adults between the ages of 18 and 54 (M = 31.73; DP = 8.75) participated in the study, divided into three groups, being, control group, depressive and schizophrenic. The control group consisted of 41.5% of women and 58.5% of men, divided between elementary school (4.9%), high school (39.6%) and higher (53.7%). Regarding the group with depression, all participants were female, with 5% of elementary school and 95% of high school. For the group with schizophrenia, the majority of the participants were male (73.2%) in relation to the female (28.8%), between elementary school (4.9%) and high school (95.1%). For the PMK evaluation, the indicatives presented by Mira (2009) were used. The quantitative results presented statistically differences from 0.001 and 0.005 for all measures and for the qualitative analysis the indicators presented χ2 values from 3.922 to 52.688. The results showed that the groups differed in both quantitative and qualitative results. The clinical groups had the highest present frequency of measurements than the control group, corroborating the results found in the original research.